(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article explores the ecological and agrarian significance of Artemisia absinthium L. (bitter wormwood) as a sustainable plant resource in the Fergana Valley, Uzbekistan. The study highlights the remarkable adaptability of wormwood to arid and saline conditions, emphasizing its role in restoring degraded soils, enhancing biodiversity, and supporting low-input agricultural systems. Using field observations and Sentinel-2 satellite imagery, the research demonstrates how wormwood contributes to soil stabilization, organic matter enrichment, and landscape resilience under water-limited environments. The plant’s leaves, rich in biologically active compounds such as thujone, absinthin, and artemisinin, further expand its potential for use in pharmaceuticals, cosmetics, and biopesticide production. Integrating Artemisia absinthium into agrarian landscapes offers both ecological and economic benefits, making it an essential component of sustainable land management and green development strategies in Central Asia.